2007
DOI: 10.1007/s10637-007-9083-2
|View full text |Cite
|
Sign up to set email alerts
|

The pharmacokinetics, toxicities, and biologic effects of FK866, a nicotinamide adenine dinucleotide biosynthesis inhibitor

Abstract: The recommended phase II dose is 0.126 mg/m2/h given as a continuous 96-h infusion every 28 days. The dose limiting toxicity of FK866 is thrombocytopenia. Pharmacokinetic data suggest an increase in the plasma Css in relation to the escalation of FK866.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
208
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 249 publications
(216 citation statements)
references
References 10 publications
8
208
0
Order By: Relevance
“…Although it is being developed as an anticancer drug, APO866 could quite easily be considered a new disease-modifying antirheumatic drug for rheumatoid arthritis. The half-life of APO866 in humans is ϳ8 hours (20), which is similar to that seen with methotrexate. Although APO866 has a potential role as a single agent for the treatment of rheumatoid arthritis, it may, similar to methotrexate, work best if administered in combination with other agents.…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations
“…Although it is being developed as an anticancer drug, APO866 could quite easily be considered a new disease-modifying antirheumatic drug for rheumatoid arthritis. The half-life of APO866 in humans is ϳ8 hours (20), which is similar to that seen with methotrexate. Although APO866 has a potential role as a single agent for the treatment of rheumatoid arthritis, it may, similar to methotrexate, work best if administered in combination with other agents.…”
Section: Discussionsupporting
confidence: 56%
“…Studies later revealed that APO866 caused NADϩ depletion through competitive inhibition of the NAMPT activity of PBEF (45). In light of the success of the inhibitory effects of APO866 in several in vivo studies, Holen et al (20) carried out an open-label, phase I clinical trial in which 26 patients with solid tumor malignancies were given escalating doses of APO866 (up to 0.126 mg/m 2 /hour, which is equivalent to our dose of 0.04 mg/kg/hour in mice). The half-life of APO866 in these human trials was between 7.9 hours and 76.5 hours.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…NAMPT inhibition can also be toxic to lymphocytes 122 , suggesting that use of NAMPT inhibitors in patients might be limited by immunosuppression. Mild lymphopenia was observed in early trials of NAMPT inhibitors, but thrombocytopenia was the dose limiting toxicity 123 . Limited clinical efficacy has been observed thus far, although work is ongoing to develop more potent compounds and define those patients most likely to benefit from NAMPT inhibition 124 .…”
Section: --Deoxyglucose (2dg) Is An Inhibitor Of Glucose Metabolism mentioning
confidence: 99%